Improvement of enzymatic hydrolysis and ethanol production from corn stalk by alkali and N-methylmorpholine-N-oxide pretreatments. (July 2016) - Cai, Ling-Yan; Ma, Yu-Long; Ma, Xiao-Xia; Lv, Jun-Min
Highlights: A combination of alkali and NMMO is a promising method for pretreatment of CS. This method removed hemicellulose and lignin and decreased cellulose crystallinity. This method increased the yield of subsequent enzymatic hydrolysis as high as 98.0%. Ethanol yield from treated CS was more than three times as compared to untreated CS. Abstract: A combinative technology of alkali and N-methylmorpholine-N-oxide (NMMO) was used to pretreat corn stalk (CS) for improving the efficiencies of subsequent enzymatic hydrolysis and ethanol fermentation. The results showed that this strategy could not only remove hemicellulose and lignin but also decrease the crystallinity of cellulose. About 98.0% of enzymatic hydrolysis yield was obtained from the pretreated CS as compared with 46.9% from the untreated sample. The yield for corresponding ethanol yield was 64.6% while untreated CS was only 18.8%. Besides, xylose yield obtained from the untreated CS was only 11.1%, while this value was 93.8% for alkali with NMMO pretreated sample. These results suggest that a combination of alkali with 50% (wt/wt) NMMO solution may be a promising alternative for pretreatment of lignocellulose, which can increase the productions of subsequent enzymatic hydrolysis and ethanol fermentation.